La production de savoir comme mode d’articulation entre acteurs publics et non publics - Silvia Bruzzone (Revue d'anthropologie des connaissances)
What is the role played by non-public actors in the study of public policies? The paper focuses on knowledge production processes in the configuration of pro-environmental groups. Knowledge production is put forward as privileged locus for interactions and articulations between the two spheres public and non public actors. This entails a pioneering notion of knowledge and expertise as neither agent’s nor institution’s attribute: it is emerging from the context, as product of situated practices. The analysis is based on a project of urban planning promoted by the environmental group Italia Nostra in the city of Milan.